Linking Entrepreneurial Competence, Motivation, and Teacher Performance in Indonesian Vocational Education: A Structural Equation Modeling Analysis (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This study examined the influence of principals' entrepreneurial competencies on teachers' motivation and performance in vocational high schools (SMKs) in Bulukumba Regency, using Covariance-Based Structural Equation Modeling (CB-SEM; AMOS v24). The structural model incorporated five dimensions of entrepreneurial competency (innovation, creativity, commitment, risk-taking, and team building), with teacher motivation as the mediating variable and teacher performance as the outcome. A sample of 200 teachers was drawn proportionally from 10 schools. Instrument validation confirmed high convergent validity and internal consistency (CRs 0.779–0.884; AVEs≥ 0.70). Model fit was evaluated using a contextual cross-index calibration approach, resulting in good fit indices (CFI = 0.989; RMSEA = 0.027; χ²(206) = 236.373, p = 0.072). Structurally, team-building (β = 0.404, p < 0.001), creativity (β = 0.165, p = 0.009), and commitment (β = 0.106, p = 0.042) showed significant direct effects on teacher performance, alongside teacher motivation (β = 0.291, p = 0.003). Motivation significantly mediated the impact of creativity on performance (t = 2.164). Collectively, this model explained 70.6% of the variance in motivation and 90.2% of the variance in performance. The novelty of this study lies in modeling the five dimensions of entrepreneurial leadership simultaneously, unlike previous research, which treated entrepreneurship as a unidimensional construct within a district-wide mediation framework. In practice, these findings suggest that leadership development programs should prioritize creativity, commitment, and team-building to enhance teacher motivation and performance in vocational education settings.